Penerapan Metode Crashing (Penambahan Tenaga Kerja Dan Jam Kerja) Pada Pembangunan Struktur Gedung Kantor Fakultas Kehutanan Universitas Tanjungpura: Penerapan Metode Crashing (Penambahan Tenaga Kerja Dan Jam Kerja) Pada Pembangunan Struktur Gedung Kantor Fakultas Kehutanan Universitas Tanjungpura - oktaviana, nanda; Arena, Azza; Werda, Werda; Hafiyyan, Qalbi (Jurusan Teknik Sipil Polnep, 2023)
The office building of the Faculty of Forestry, University of Tanjungpura was built to improve existing facilities and infrastructure. This building is also needed to support academic and non-academic activities of students. So that the building can be used immediately, then the acceleration of time on the construction of the building. This study aims to determine the cost and time of the project due to the acceleration (crashing). The acceleration is carried out by the method of crashing. Calculation of crashing with the alternative addition of the number of workers and working hours (overtime). Where the addition of the number of workers is increased by 15% than the normal number of workers and the addition of working hours (overtime) is done for 3 hours. Calculation of crashing using the alternative addition of the number of workers and the addition of working hours (overtime). Normally, this project requires a cost of Rp 2,410,298,907.92, the duration of the work for 1169 days and a workforce of 525 people. The calculation results with the alternative addition of the number of workers as many as 79 people, requires a cost of Rp 2,419,883,466.82. The time required is 1011 days (158 days more than normal). As for the calculation with the alternative addition of working hours (overtime), the cost of Rp 2,432,295,278.89 and the required duration is 890 days (279 days faster than normal). Based on the calculation results, the addition of Labor and working hours proved to accelerate the implementation time of the project. However, this will also increase the cost of the project.